How do you differentiate #e^(2x^2+x) # using the chain rule?

1 Answer
Jun 17, 2017

Answer:

#d/dx=e^(2x^2+x)(4x+1)#

Explanation:

The derivative of #e^x# is itself.
When you differentiate #e^x# you take the derivative of #x# basically you take the derivative of whatever #x# may be.

#d/dx=e^(2x^2+x)=e^(2x^2+x)#

Then take the derivative of what's inside:

#d/dx(2x^2+1)=4x+1#

Now you multiply them:

#d/dx=e^(2x^2+x)(4x+1)#

#d/dx=4e^(2x^2+x)x+e^(2x^2+x)#

Put you can simply leave it as:

#d/dx=e^(2x^2+x)(4x+1)#